Tumor-Associated Regulatory T Cells in Non-Small-Cell Lung Cancer: Current Advances and Future Perspectives - Jiaqi Liang; Guoshu Bi; Guangyao Shan; Xing Jin; Yunyi Bian; Qun Wang (Journal of Immunology Research)
Non-small-cell lung cancer (NSCLC) is one of the most threatening malignant tumors to human health, with the overall 5-year survival rate being less than 30%. Regulatory T cells (Tregs), a functional subset of T cells, maintain immunologic immunological self-tolerance and homeostasis. Accumulating evidence has uncovered their implicated roles in various cancers in recent years. In NSCLC, they are associated with staging, therapeutic efficacy, and prognosis by infiltrating in tissues and thereby attenuating immunologic anticancer effects in patients. Tumor-associated Tregs display distinct immune signatures in NSCLC compared to thymus-derived Tregs, playing an important role in remodeling the tumor microenvironment (TME). Targeting Tregs has become a novel direction for NSCLC patients, such as disrupting their immune-suppressive functions, blocking their trafficking into tumors, and inhibiting their development and/or activation. This review is aimed at elucidating the molecular mechanisms of tumor-associated Tregs in NSCLC and providing therapeutic targets relevant to Tregs.